2019
DOI: 10.1029/2018gl080771
|View full text |Cite
|
Sign up to set email alerts
|

Estimating River Discharge With Swath Altimetry: A Proof of Concept Using AirSWOT Observations

Abstract: The forthcoming Surface Water and Ocean Topography (SWOT) satellite mission will provide global measurements of the free surface of large rivers, providing new opportunities for remote sensing‐derived estimates of river discharge in gaged and ungaged basins. SWOT discharge algorithms have been developed and benchmarked using synthetic data but remain untested on real‐world swath altimetry observations. We present the first discharge estimates from AirSWOT, a SWOT‐like airborne Ka‐band radar, using 6 days of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 42 publications
6
76
2
Order By: Relevance
“…A key SWOT mission objective is to obtain water surface elevation (WSE) to ±10 cm vertical accuracy for 1 km 2 open water regions [66]. Previous work used CIR-derived water masks and spatially-averaged AirSWOT Ka-band interferometric radar data to estimate AirSWOT WSE accuracies of~9-10 cm in rivers and~21 cm in lakes [53,[67][68][69]. The conservative AirSWOT color-infrared (CIR) water mask provided here should enable unambiguous extraction of open water pixels used for spatial averaging of AirSWOT interferometric radar data, and, therefore, improve estimates of WSE accuracy (Figure 10).…”
Section: Utility Of Cir Open Water Classifications For the Swot Satelmentioning
confidence: 99%
“…A key SWOT mission objective is to obtain water surface elevation (WSE) to ±10 cm vertical accuracy for 1 km 2 open water regions [66]. Previous work used CIR-derived water masks and spatially-averaged AirSWOT Ka-band interferometric radar data to estimate AirSWOT WSE accuracies of~9-10 cm in rivers and~21 cm in lakes [53,[67][68][69]. The conservative AirSWOT color-infrared (CIR) water mask provided here should enable unambiguous extraction of open water pixels used for spatial averaging of AirSWOT interferometric radar data, and, therefore, improve estimates of WSE accuracy (Figure 10).…”
Section: Utility Of Cir Open Water Classifications For the Swot Satelmentioning
confidence: 99%
“…We use a 0.5 km 2 window, while Altenau et al use 1 km 2 areas. Tuozzolo et al [30] reported RMSE of 11.6 cm compared to in situ data over the Willamette River, Oregon, when using a 1 km shifting window to perform the averaging. Pitcher et al [29] tested window sizes of both 1 km 2 and 0.0625 km 2 for a study in the Yukon Flats Basin in Alaska, and reported RMSE values of 8 and 15 cm, respectively, for rivers only.…”
Section: Water Surface Elevationmentioning
confidence: 99%
“…Early studies had demonstrated the feasibility and potential of Ka-band InSAR for mapping water surfaces, using both ground-based [24] and airborne radar experiments [25,26]. Recent studies have demonstrated the capabilities of AirSWOT to measure rivers and lakes [27][28][29][30][31]. Altenau et al [27] used AirSWOT data to measure WSE, WSS, and estimate discharge [28] along the Tanana River, Alaska, USA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations